The Changing Nature of Irish Wage Inequality from Boom to Bust - Niamh Holton; Donal O'Neill (Institute for the Study of Labor (IZA), 2015)
The dramatic change in economic conditions in Ireland over the last 10 years provides an opportunity to examine the impact of large macroeconomic shocks on inequality. We analyse wage inequality in Ireland from the height of an economic boom, through a very deep recession, to the start of a recovery. In keeping with previous work we find that dispersion in wages increased towards the height of the boom, driven largely by rising returns to skills. However, the economic crisis of 2008-2013 was accompanied by a significant reduction in earnings dispersion. Although the improving characteristics of the work force increased wages for everyone over this period, these increases were offset by falling returns to skills. Only workers in the lowest decile were unaffected by the declining returns, resulting in wage growth at the bottom of the distribution and a decline in inequality during the recession.
Keywords: J31; 330; inequality; composition bias; returns to skill